The impact of green HRM on green creativity and green empowerment: Evidence from the UAE - Thabit, Ruqaya Ahmed Mohamed; Shneikat, Belal; Allozi, Abdelwahhab (International Journal of Innovative Research and Scientific Studies, 2025)
This study examines the impact of Green Human Resource Management (GHRM) on Green Creativity (GC) and Green Empowerment (GE) within the hospitality sector in the United Arab Emirates (UAE). The study further explores the moderating role of intrinsic rewards on these relationships to enhance understanding of employee-driven sustainability initiatives. A quantitative research design was employed using purposive sampling to collect data from frontline employees at 4- and 5-star hotels in Dubai. A structured questionnaire was used to measure GHRM, GC, GE, and intrinsic rewards. Statistical analyses, correlation, regression, and moderated mediation tests were conducted to test hypotheses. The results reveal that GHRM positively influences both GC and GE. Furthermore, GE mediates the relationship between GHRM and GC. Intrinsic rewards were found to moderate the relationship between GHRM and GC but not between GHRM and GE. These results highlight the psychological mechanisms through which HR practices can stimulate green innovation and employee engagement in sustainable practices. The research contributes to the growing literature on sustainable HR practices by establishing GHRM as a critical enabler of green creativity and empowerment in the hospitality industry. It emphasizes the role of intrinsic motivation in enhancing the effectiveness of GHRM interventions. The findings offer actionable insights for HR practitioners and organizational leaders. By embedding sustainability into HR functions and leveraging intrinsic rewards, organizations can cultivate a workforce that is both innovative and environmentally conscious. This approach is particularly relevant for hotels aiming to align with global sustainability goals and enhance their competitive positioning.